TANTANGAN, DUKUNGAN, DAN KEPUASAN DALAM MERAWAT PASIEN COVID-19: STUDI FENOMENOLOGI TERHADAP PERAWAT DI KOTA TANGERANG SELATAN - Candra Putra; Dyah Juliastuti (Jurnal Kesehatan STIKes IMC Bintaro, 2021)
The number of new cases and deaths from COVID-19 continues to increase. The COVID-19 infection has become a worldwide pandemic. Nurses are one of the frontline health workers in providing care for patients infected with COVID-19. This study aims to identify the experiences of nurses providing care for COVID-19 patients. Qualitative data obtained through in-depth interviews to four nurses at a private hospital in South Tangerang, Banten, Indonesia, were thematically analysis. Five themes were identified in this study, namely: the meaning of infection and care, loyalty and supports in caring for patients, challenges in caring for patients, satisfaction in caring for patients, and maintaining personal health. To conclude, nurses as the frontline in handling COVID-19 have an important role and function in the healing process of COVID-19 patients. It is expected that nurses who provide services to COVID-19 patients will get physical and mental support from their working institution, families, and community to manage the challenge in nursing COVID-19 patient, and provide optimal and effective care services.